Tips for Integrating Land and Wildlife Management: Quail and Timber - William M. Giuliano; Lauren Watine (EDIS)
In Florida, changes in forest management practices during the past 50+ years have led to declines in quail habitat and populations. Important changes involve the use of fire and conversion of native forests to commercial pine plantations. A lack of fire and other disturbance has often led to closed-canopy forests with dense undergrowth that lack important quail habitat components. This 2-page fact sheet provides several quail habitat improvement tips that focus on diversifying the plant species and structural composition and increasing early successional communities dominated by herbaceous plants. Written by William M. Giuliano and Lauren Watine and published by the UF Department of Wildlife Ecology and Conservation, January 2013.